Ancaman, Faktor Protektif, dan Resiliensi Remaja di Kota Bogor - Maesaroh, Siti; Sunarti, Euis; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Adolescents are vulnerable to risky behavior so adolescents must have resilience or ability to face challenging, changing, and difficult situations that are impossible to avoid in human life. This study aimed to analyze factors that influence adolescents’ resilience in Bogor city. This study was conducted at Senior High School and Vocational High School that were purposively selected. Samples in this study were 240 adolescents, chosen by disproportional stratified random sampling. The results of this study showed that there is significant difference in internal protective factors between adolescents of senior high school and vocational high school. Adolescents of the senior high school had higher self-efficacy, goals, and aspiration than adolescents of vocational high school. Furthermore, the external protective factor of family dimension had significant difference between senior high school and vocational high school adolescents. Moreover, there was significant difference in self-acceptance dimension of resilience between senior high school and vocational high school adolescents. The resilience of adolescents was significantly affected by internal protective factors (empathy, self-awareness, goals, and aspiration) and external protective factors (family, society, and peer group).